Human Immunodeficiency Virus Playing Hide-and-Seek: Understanding the TFH Cell Reservoir and Proposing Strategies to Overcome the Follicle Sanctuary - Leong, Yew Ann; Atnerkar, Anurag; Yu, Di (Frontiers in Immunology, 2017)
Human immunodeficiency virus (HIV) infects millions of people worldwide and new cases continue to emerge even when effective preventative measures are available. Once infected, the virus cannot be eliminated by the immune system. The disease progresses in majority of the patients that eventually lead to acquired immunodeficiency syndrome (AIDS). Combination anti-retroviral therapeutic regimen effectively suppresses viral replication in the body and halt disease progression. The treatment, however, only suppresses viral replication but do not eliminate the virus-infected cells. Moreover, interruption of treatment inevitably leads to immediate viral rebound and disease progression. The rebound virus comes from a group of virus-infected cells, which are called the cellular reservoir of HIV. Identifying and eliminating the cellular reservoir of HIV will prevent viral rebound, i.e. the cure of chronic HIV infection. In this review, we focus on a recently discovered HIV reservoir in a subset of CD4+ T cells called the follicular helper T (TFH) cells. We describe the relevance of this CD4+ T cell subset to the viral reservoir and viral rebound, the potential mechanisms for the emergence of reservoir in TFH cells, and the potential strategies to target and eliminate this viral reservoir.